The Epistemology of Text Understanding in the View of ‘Abd al-Qāhir al-Jurjānī: The Discourse of lafaẓ and ma’nā - Ahmad Hifni (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2024)
Purpose – This article examines the thoughts of 'Abdul al-Qāhir al-Jurjānī (d. 471/474 H) in looking at the relationship between pronunciation (text) and meaning and explains his thoughts in an effort to build a moderate understanding of the text. Al-Jurjānī's view can be said to be distinctive, because it is different from the thinking of Arab linguists in general who see each word as having its own meaning. Al-Jurjānī, offers another view by saying that a single vocabulary does not have meaning in itself, but rather because of its interaction (structure/nazam) with other vocabulary. Meanwhile, a word is a marker/symbol (signifier) for a meaning/concept (signified). This view attracted the attention of language intellectuals from various eras, and even inspired intellectual thought from various other scientific disciplines, including commentators in studying and exploring the more moderate meaning of the Alquran. Design/methods/approach – This research uses qualitative methods enriched by knowledge of social sciences and humanities with various scientific disciplines such as sociology and history as a basis for philosophical traditions to contribute to aspects outside the study of texts. The primary source for this article is the book entitled Dalāil al-I'jaz and Asrār al-Balāghah by al-Jurjānī. This research is based on library research; by reviewing library materials, in the form of scientific journals, books, encyclopedias and other sources relevant to the topic being studied. Findings – This article concludes that al-Jurjānī was the founder of the theory of classical structuralism and semiotics in Islamic literature, with his theory called nazam. Research implications – The findings in this article can become a foundation and thinking paradigm for readers and text reviewers to build a moderate discourse and understanding of the text that is understood by the readers.